1987
DOI: 10.1677/joe.0.1120367
|View full text |Cite
|
Sign up to set email alerts
|

A possible dual regulation of prolactin release by the serotoninergic system in rats at pro-oestrus and during late pregnancy: role of ovarian hormones

Abstract: The effect of para-chlorophenylalanine (pCPA), an inhibitor of serotonin synthesis, on prolactin release was studied in rats on the day of pro-oestrus and at the end of pregnancy (day 19). The surges of prolactin normally seen in the afternoon of pro-oestrus in intact rats and in rats ovariectomized on dioestrous day 2 and primed with oestrogen were significantly inhibited by pCPA treatment. Administration of 5-hydroxytryptophan reversed the inhibitory action of pCPA on prolactin release. Treatment with proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
(43 reference statements)
1
7
1
Order By: Relevance
“…This finding is consistent with other studies showing that not only estradiol but also progesterone can alter serotonergic neurotransmission. A stimulatory role for progesterone in the regulation of 5-HT synthesis has been demonstrated (Jahn and Deis, 1987), even though progesterone appears to have no effect on the translation of the serotonin-synthesizing enzyme, tryptophan hydroxylase (Bethea et al, 2000). Our data show that progesterone, similar to estrogen, interferes with the ability of an SSRI to block SERT function.…”
Section: Discussionmentioning
confidence: 48%
“…This finding is consistent with other studies showing that not only estradiol but also progesterone can alter serotonergic neurotransmission. A stimulatory role for progesterone in the regulation of 5-HT synthesis has been demonstrated (Jahn and Deis, 1987), even though progesterone appears to have no effect on the translation of the serotonin-synthesizing enzyme, tryptophan hydroxylase (Bethea et al, 2000). Our data show that progesterone, similar to estrogen, interferes with the ability of an SSRI to block SERT function.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, P partially blocks the effect of pCPA, a serotonin synthesis inhibitor, on hypothalamic serotonin levels, and an antiprogestin reduced hypothalamic levels of 5HIAA, a serotonin metabolite (Walker and Wilson, 1983). Moreover, the proestrus surge of prolactin is inhibited by pCPA treatment, and this effect is completely reversed by P treatment (Jahn and Deis, 1987). Together, these data support a stimulatory role for P in the regulation of serotonin synthesis.…”
Section: Relation To Other Studiesmentioning
confidence: 58%
“…Blood samples were taken 35 h after pCPA injection (at 18.00 h on days 3, 6, or 17, respectively). Results from our laboratory have shown previously [14] that, under these conditions, pC'PA modifies the PRL concentra tions in pregnant rats. It has been shown also that lower doses of pC'PA (i.c.. 150 mg/kg) can decrease significantly the concentration of the metabolite of serotonin, 5-hydroxyindoleacetic acid, in cere brospinal fluid of conscious rats 24 h later [21 ].…”
Section: Drug Treatmentsmentioning
confidence: 66%
“…The most important neurotransmit ters stimulating PRL secretion are the opioid peptides [11. 12] and serotonin [13][14][15], It has been shown that in the arcuate nucleus the neurons responsible for producing opioid peptides are able to concentrate estrogens [ 16], On the other hand, serotonin neurons participate in the proestrous surge of PRL and in the PRL secretion in duced by administration of estrogen to ovariectomized rats, while progesterone enhances these actions [17], However, it has been shown that both serotoninergic [14,15] and opioid [18,19] systems may inhibit PRL secre tion under certain conditions. The aim of this study was to determine the pattern of PRL secretion induced by the central action of estradiol and the participation of opioid and sertoninergic systems in regulating this secretion.…”
Section: Introductionmentioning
confidence: 99%